The Hubungan Infeksi Saluran Pernafasan Akut dengan Kejadian Stunting - Naza Tsasbita Hayuning Adila (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction; stunting is a nutritional problem because it can increase morbidity and mortality, cognitive decline, motor skills, language development, learning abilities, and work capacity. Objective: To determine the relationship between ARI and the incidence of stunting. Methods: Using the literature by searching for the keywords stunting, acute respiratory infections, and acute respiratory infections on Google Scholar and Pubmed. A literature search from both national and international journals then summarizes the topics of discussion and compares the results presented in the articles. Result; Infection increases energy requirements to lead to immunity and cellular repair. Inadequate energy intake due to decreased appetite and malabsorption exacerbates this condition. The imbalance between demand and income causes children to fall into a stunted state. Conclusion: there is a relationship between acute respiratory infections and the incidence of stunting.